Negative electrode sheet and device including the negative electrode sheet
A structured negative electrode sheet with a ferroelectric particle layer addresses the issue of lithium dendrite formation in secondary batteries, enhancing cycle performance and safety by ensuring uniform metal ion distribution.
Patent Information
- Application Number
- JP2024543096
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-07-14
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2042-07-14
AI Technical Summary
The rapid charging of secondary batteries can lead to reduced cycle performance and the formation of lithium dendrites, which can cause internal short circuits and safety risks.
A negative electrode sheet with a structured design, including a negative electrode film layer and a ferroelectric particle layer, is implemented to ensure uniform distribution of metal ions, thereby preventing lithium dendrite formation and enhancing cycle performance.
The structured negative electrode sheet ensures uniform metal ion distribution, reducing the risk of lithium dendrites and improving the cycle performance and safety of secondary batteries while maintaining high energy density.
Smart Images

Figure 2025503038000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the field of batteries, and in particular to negative electrode sheets and devices including negative electrode sheets. [Background technology]
[0002] Since secondary batteries have characteristics such as high capacity and long life, they are widely used in electronic devices such as mobile phones, notebook computers, electric scooters, electric cars, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes, electric tools, etc. As the range of applications of batteries becomes wider, the requirements for the performance of secondary batteries are becoming more and more stringent, for example, rapid charging capability is required.
[0003] However, while improving the rapid charging capability of the secondary battery, it may also reduce the cycle performance of the secondary battery due to the risk of lithium precipitation, etc. Summary of the Invention
[0004] The present application has been made in consideration of the above-mentioned problems, and has an object to provide a negative electrode sheet and a device including the negative electrode sheet.
[0005] A first aspect of the present application provides a negative electrode sheet for a secondary battery, the negative electrode sheet comprising: a negative electrode current collector; a negative electrode film layer provided on at least one surface of the negative electrode current collector and containing a negative electrode active material; and a ferroelectric layer provided on a surface of the negative electrode film layer away from the negative electrode current collector and containing ferroelectric particles, the negative electrode film layer having a compressed density of Pg / cm 3 and the coating weight of the negative electrode film layer is CWg / 1540.25mm 2 The thickness of the ferroelectric layer is H μm, the volume average particle size Dv50 of the ferroelectric particles is D μm, and the negative electrode sheet is JPEG2025503038000002.jpg1869, preferably Meet JPEG2025503038000003.jpg1771.
[0006] Thus, in the present application, when the compressed density P of the negative electrode film layer, the coating weight of the negative electrode film layer, the thickness H of the ferroelectric layer, and the volume average particle size Dv50 of the ferroelectric particles are controlled to satisfy the above ranges, when the negative electrode sheet is applied to a secondary battery and the secondary battery is charged, it can ensure that the ferroelectric particles in the ferroelectric layer fully exert the ferroelectric effect, uniformly distribute the metal ions between the negative electrode active material and the electrolyte interface, ensure the lithium insertion ability of the negative electrode sheet, and improve the cycle performance of the secondary battery applied to the negative electrode sheet.
[0007] In some embodiments, the thickness H μm of the ferroelectric layer satisfies 2≦H≦10, preferably 4≦H≦6.
[0008] When the thickness H of the ferroelectric layer satisfies the above range, the ferroelectric layer can fully exert the ferroelectric effect during the charging process of the secondary battery, and the distribution of metal ions can be more balanced and more uniform. In addition, the volume occupied by the ferroelectric layer in the above thickness range is not too large, so that the space in the secondary battery is not excessively eroded, and the space occupied by the negative electrode active material can be ensured, so that the energy density and capacity of the secondary battery can be ensured, and the secondary battery can have a long driving range. In addition, when the thickness of the ferroelectric layer is appropriate, the vertical growth of metal ions can be effectively inhibited, and the risk of short circuiting inside the secondary battery can be effectively reduced when the secondary battery is charged at a high rate, so that the high rate charging performance of the secondary battery can be ensured.
[0009] In some embodiments, the volume average particle diameter Dv50 of the ferroelectric particles satisfies 0.08≦D≦1, preferably 0.1≦D≦0.8. When the volume average particle diameter Dv50 of the ferroelectric particles satisfies the above range, it is advantageous for the ferroelectric particles to be uniformly distributed in the ferroelectric layer.
[0010] In some embodiments, the mass content a of the ferroelectric particles satisfies 90%≦a≦98%, preferably 95%≦a≦98%, based on the total mass of the ferroelectric layer. When the mass content a of the ferroelectric particles satisfies the above range, the ferroelectric particles are more uniformly distributed on the surface of the negative electrode film layer, and the generated reverse electric field becomes more uniform.
[0011] In some embodiments, the ferroelectric particles include one or more selected from perovskite structure oxides, tungsten bronze type compounds, and bismuth oxide type layered structure compounds. The perovskite structure oxides include one or more of barium titanate BTO, lead zirconate titanate PZT, lead metaniobate, barium lithium lead niobate PBLN, and lead titanate PT. The above types of ferroelectric particles can effectively exert the ferroelectric effect and increase the uniform distribution degree of metal ions.
[0012] In some embodiments, the dielectric constant of the ferroelectric particles satisfies 100≦ε≦100000, preferably 1000≦ε≦10000. When the dielectric constant of the ferroelectric particles is in the above range, it can rapidly move metal ions and ensure the movement speed of the metal ions.
[0013] In some embodiments, the negative electrode film layer has a compressive density Pg / cm at an applied force of 20,000 N. 3 and the coating weight of the negative electrode film layer CWg / 1540.25mm 2 The relationship between the JPEG2025503038000004.jpg2051
[0014] When the compression density P and coating weight CW of the negative electrode film layer are within the above range, it can be ensured that the negative electrode film layer is within an appropriate thickness range, and thus the energy density of the secondary battery can be ensured. When Z is within the above range during the charging process of the secondary battery, the ferroelectric layer has an effect on the entire structure of the pole piece, including the structure of the lower layer of the pole piece. In addition, the pole piece has an appropriate void, and the electrolyte is sufficiently infiltrated into the pole piece, which is favorable for the movement of lithium ions.
[0015] In some embodiments, the compressed density of the negative electrode membrane layer is Pg / cm 3 satisfies 1.10≦P≦1.85, preferably 1.30≦P≦1.80. By adjusting the compression density of the negative electrode film layer within an appropriate range, the energy density of the secondary battery can be increased. In addition, by adjusting the compression density within an appropriate range, the negative electrode film layer has the ability to maintain a strong channel structure during the cycle process, which improves the wettability of the electrolyte of the negative electrode sheet, and can better improve the cycle performance of the secondary battery.
[0016] In some embodiments, the coating weight of the negative electrode film layer is CWg / 1540.25 mm 2 The coating weight CW of the negative electrode film layer is adjusted within a suitable range to ensure the energy density of the electric core and the effect of the ferroelectric layer on the negative electrode film layer.
[0017] In some embodiments, the thickness L μm of the negative electrode film layer satisfies 30 μm≦L≦200 μm, preferably 35 μm≦L≦190 μm. By adjusting the thickness L of the negative electrode film layer within a suitable range, the quality of the negative electrode active material can be ensured, and the energy density of the secondary battery can be ensured, while the ferroelectric layer can cooperate with the ferroelectric layer to fully exert the ferroelectric effect, and the uniform distribution of metal ions in the negative electrode film layer can be promoted.
[0018] In some embodiments, the negative electrode active material comprises one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate.
[0019] A second aspect of the present application further provides a secondary battery including a negative electrode sheet according to any one of the embodiments of the first aspect of the present application.
[0020] A third aspect of the present application further provides a battery module including a secondary battery according to the embodiment of the second aspect of the present application.
[0021] A fourth aspect of the present application further provides a battery pack including a battery module according to an embodiment of the third aspect of the present application.
[0022] A fifth aspect of the present application further provides a power consuming device including the secondary battery of an embodiment of the second aspect of the present application, the battery module of an embodiment of the third aspect of the present application, or the battery pack of an embodiment of the fourth aspect of the present application. [Brief description of the drawings]
[0023] In order to more clearly explain the technical solutions of the embodiments of the present application, the following briefly introduces drawings required in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can also obtain other drawings based on the drawings without any creative efforts.
[0024] [Figure 1] FIG. 2 is a schematic diagram of a negative electrode sheet according to one embodiment of the present application. [Diagram 2] FIG. 2 is a schematic cross-sectional view taken along line AA of the negative electrode sheet shown in FIG. [Diagram 3] FIG. 1 is a schematic diagram of an electrode assembly according to one embodiment of the present application. [Figure 4] FIG. 1 is a schematic diagram of a secondary battery according to one embodiment of the present application. [Diagram 5] FIG. 5 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG. 4. [Figure 6] FIG. 1 is a schematic diagram of a battery module according to one embodiment of the present application. [Figure 7] FIG. 1 is a schematic diagram of a battery pack according to one embodiment of the present application. [Figure 8] FIG. 8 is an exploded view of the battery pack shown in FIG. 7 according to one embodiment of the present application. [Figure 9] 1 is a schematic diagram of a power consuming device according to one embodiment of the present application.The drawings are not necessarily drawn to scale.
[0025] The symbols are explained as follows: 1 Battery pack 2 Upper case 3 Lower housing 4 Battery Module 5 Secondary battery 51 cases 52 Electrode Assembly 521 Negative electrode sheet 522 Positive electrode sheet 523 Separator 5211 Negative electrode current collector 5212 Negative electrode film layer 5213 Ferroelectric layer 53 Cover plate 6 Power consumption equipment DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, the embodiments specifically disclosing the negative electrode sheet and the device including the negative electrode sheet of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of already well-known matters and duplicate description of substantially the same configuration may be omitted. This is to avoid the following description becoming unnecessarily redundant and to facilitate understanding by those skilled in the art. Note that the attached drawings and the following description are provided to enable those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0027] The "ranges" disclosed herein are defined in the form of lower and upper limits, where a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits specifically define the boundaries of the range. Ranges defined in this manner may or may not include the endpoints and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, by reciting ranges of 60-120 and 80-110 for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. Also, by reciting minimum range values 1 and 2 and maximum range values 3, 4 and 5, the ranges 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5 are all contemplated. In this application, unless otherwise stated, a numerical range "a-b" refers to a contraction of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0 to 5" indicates that all real numbers between "0 and 5" are listed herein, and "0 to 5" is a contraction of combinations of these numerical values. In addition, when a parameter is expressed as an integer ≧2, this is equivalent to disclosing that the parameter is an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0028] Unless otherwise stated, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise stated, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0029] Unless otherwise stated, all steps in the present application may be performed in sequence, may be performed randomly, and are preferably performed in sequence. For example, a method comprising steps (a) and (b) indicates that the method may comprise steps (a) and (b) performed in sequence, or may comprise steps (b) and (a) performed in sequence. For example, a method may further comprise step (c) indicates that step (c) may be added to the method in any order, e.g., the method may comprise steps (a), (b), and (c), may comprise steps (a), (c), and (b), may further comprise steps (c), (a), and (b), etc.
[0030] Unless otherwise stated, the terms "comprising" and "including" referred to in this application may be open ended or closed ended. For example, "comprising" and "including" indicate that the term may comprise or include other components not further recited, or may comprise or include only the recited components.
[0031] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions satisfy the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or A and B are both true (or exist).
[0032] As used herein, the terms "plurality" and "multiple types" refer to two or more than two types.
[0033] In the present application, the secondary battery may include a lithium ion battery, a lithium sulfur battery, a sodium lithium ion battery, a sodium ion battery, a magnesium ion battery, etc., but the embodiments of the present application are not limited thereto.
[0034] A secondary battery includes an electrode assembly and an electrolyte, and the electrode assembly is composed of a positive electrode sheet, a negative electrode sheet, and a separator. The secondary battery is mainly operated by the movement of metal ions between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes a positive electrode active material, and the negative electrode sheet includes a negative electrode active material. Here, the metal ions can be lithium ions, sodium ions, etc., and the charging process will be described below assuming that the metal ions are lithium ions.
[0035] In the charging process of a secondary battery, the electrode kinetic process usually includes several steps:
[0036] (1) Lithium ion desorption step: Lithium ions are desorbed from the positive electrode active material and transferred to the electrolyte phase. (2) Liquid phase mass transfer step in the electrolyte phase: The solvated lithium ions in the electrolyte are diffused and transferred to the surface of the negative electrode active material. (3) Surface conversion step: During the first charge, the solvated lithium ions are adsorbed on the surface of the negative electrode active material and react to form a solid electrolyte interface (SEI) film. During the subsequent charge process, the solvated lithium ions are adsorbed on the surface of the SEI film, and the lithium ions reach the surface of the negative electrode active material through a desolvation process. (4) Charge exchange step: The lithium ions obtain electrons from the surface of the negative electrode active material to form a lithium insertion product. (5) Lithium insertion product solid phase mass transfer step: The lithium insertion product diffuses in the solid phase from the surface of the negative electrode active material to the inside, completing the charging process.
[0037] With the increase in the charging rate, lithium ions may rapidly desorb from the positive electrode active material, and there may be unevenness in the current density and the lithium ion concentration distribution in the electrolyte phase, which makes it easy for the lithium ions in the electrolyte phase to concentrate locally on the surface of the negative electrode active material, and the lithium ions desorbed from the positive electrode active material are not inserted into the negative electrode active material in equal amounts, and the lithium ions that are not inserted into the negative electrode active material gain electrons on the surface of the negative electrode active material to form silver-white metallic lithium elements, i.e., "lithium dendrites". The formation of lithium dendrites not only reduces the performance of the secondary battery, such as shortening the cycle life, but also in serious cases, may form sharp shapes to pierce the separator and short-circuit the secondary battery, causing catastrophic consequences such as combustion and explosion. At the same time, the metallic lithium elements that are constantly deposited fall off the surface of the negative electrode active material, forming "dead lithium" that cannot participate in the reaction, which reduces the energy density of the secondary battery.
[0038] Therefore, the inventors propose a negative electrode sheet including a ferroelectric layer that can improve the problems of "lithium dendrites" and "dead lithium" by improving the negative electrode sheet and uniformly inserting metal ions, such as lithium ions, into the negative electrode active material, thereby improving the cycle performance of a secondary battery including the negative electrode sheet and improving the rapid charging performance of the negative electrode sheet.
[0039] Negative electrode sheet
[0040] According to a first aspect, the present application provides a negative electrode sheet.
[0041] As shown in FIG. 1 and FIG. 2, the negative electrode sheet 521 includes a negative electrode current collector 5211, a negative electrode film layer 5212 provided on at least one surface of the negative electrode current collector 5211, and a ferroelectric layer 5213, the negative electrode film layer 5212 including a negative electrode active material, the ferroelectric layer 5213 being provided on a surface of the negative electrode film layer 5212 away from the negative electrode current collector 5211, the ferroelectric layer 5213 including ferroelectric particles, and the compressed density of the negative electrode film layer 5212 is Pg / cm 3and the coating weight of the negative electrode film layer 5212 is CWg / 1540.25mm 2 The thickness of the ferroelectric layer 5213 is H μm, the volume average particle diameter Dv50 of the ferroelectric particles is D μm, and the secondary battery is JPEG2025503038000005.jpg1876, preferably Meet JPEG2025503038000006.jpg2069.
[0042] For ease of explanation, Let's say JPEG2025503038000007.jpg1857.
[0043] The negative electrode current collector 5211 has both sides opposed to each other in the thickness direction thereof, and the negative electrode film layer 5212 may be provided on either or both of the two opposed surfaces of the negative electrode current collector 5211. The negative electrode current collector 5211 may be a copper foil or a composite current collector, but this application is not limited thereto.
[0044] The ferroelectric layer 5213 includes ferroelectric particles, and may of course further include other auxiliary agents, such as adhesives, etc. When the ferroelectric layer 5213 includes ferroelectric particles, the ferroelectric particles can be directly provided on the surface of the negative electrode film layer 5212. When the ferroelectric layer 5213 further includes other auxiliary agents, the ferroelectric particles can be provided on the surface of the negative electrode film layer 5212 by adhesives, etc.
[0045] Although the mechanism is unclear, the inventors have discovered that the negative electrode sheet 521 of the present application has good dynamic performance, can effectively mitigate the metal deposition phenomenon, and can improve the fast charging capability of the secondary battery.
[0046] The inventors speculate that the mechanism is as follows. The ferroelectric particles have a ferroelectric effect due to the spontaneous polarization direction and intensity of the ferroelectric material and the corresponding unit lattice parameters changing in an external electric field. In other words, the ferroelectric effect refers to the generation of charges on the surface of the ferroelectric particles when the ferroelectric particles are subjected to the action of an external electric field. In the present application, during the charging process of the secondary battery, there is an internal electric field between the positive electrode sheet and the negative electrode sheet 521, and the internal electric field excites the ferroelectric particles to generate a ferroelectric effect, causing the center of the positive and negative charges inside the ferroelectric particles to shift, generating a reverse electric field opposite to the internal electric field, and the reverse electric field balances the electron density on the surface of the negative electrode active material, thereby uniforming the metal ion distribution between the negative electrode active material and the electrolyte interface, that is, uniforming the concentration distribution of the metal ions between the negative electrode active material and the electrolyte interface, thereby allowing the metal ions to be uniformly inserted into the negative electrode active material, reducing the risk of metal precipitation due to localized concentration of metal ions, reducing the loss of metal ions, and ensuring the cycle performance of the secondary battery. In the present application, the risk of localized precipitation of metal ions is reduced, and taking the metal ions as an example, lithium ions are used to reduce the risk of lithium ions being precipitated, the risk of lithium dendrites being generated, and the risk of lithium dendrites breaking through the separator to cause an internal short circuit in the secondary battery are reduced, thereby improving the safety performance of the secondary battery. In addition, the energy barrier when the metal ions move into the negative electrode active material through the ferroelectric particles is relatively low, and the movement speed is relatively fast, so that the rapid charging performance of the negative electrode sheet 521 can be ensured.
[0047] In addition, the ferroelectric particles can further reduce the volume expansion of the negative electrode film 5212, protect the structure of the negative electrode film 5212, and ensure the cycle stability of the negative electrode film 5212, thereby ensuring the cycle stability of the secondary battery.
[0048] In the present application, when the compressed density P of the negative electrode film layer 5212, the coating weight of the negative electrode film layer 5212, the thickness H of the ferroelectric layer 5213, and the volume average particle size Dv50 of the ferroelectric particles satisfy the above ranges, and the negative electrode sheet 521 is applied to a secondary battery, it can ensure that the ferroelectric particles in the ferroelectric layer 5213 can fully exert the ferroelectric effect when the secondary battery is charged, and can uniformly distribute the metal ions between the negative electrode active material and the electrolyte interface, ensure the lithium insertion ability of the negative electrode sheet 521, and improve the cycle performance of the secondary battery to which the negative electrode sheet 521 is applied.
[0049] In some embodiments, the thickness H μm of the ferroelectric layer 5213 satisfies 2≦H≦10.
[0050] When the thickness H of the ferroelectric layer 5213 satisfies the above range, the ferroelectric layer 5213 can fully exert the ferroelectric effect during the charging process of the secondary battery, and the distribution of the metal ions can be more balanced and more uniform. In addition, since the ferroelectric layer 5213 may not be able to provide capacity to the secondary battery, the occupied volume of the ferroelectric layer 5213 in the above thickness range is not too large, and does not excessively erode the space in the secondary battery, and can ensure the occupied space of the negative electrode active material, thereby ensuring the energy density and capacity of the secondary battery, and allowing the secondary battery to have a long driving range. In addition, if the thickness of the ferroelectric layer 5213 is appropriate, it can effectively ensure the effect of suppressing the vertical growth of the metal ions, and can effectively reduce the risk of short circuiting inside the secondary battery when the secondary battery performs high-power charging, thereby ensuring the high-power charging performance of the secondary battery. Preferably, the thickness of the ferroelectric layer 5213 satisfies 4≦H≦6. Exemplarily, the thickness of the ferroelectric layer 5213 may be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm, or a range consisting of any two of the above values.
[0051] The thickness H of the ferroelectric layer 5213 has a meaning known in the art and can be measured using a test device and a test method known in the art. For example, the thickness of the negative electrode sheet 521 at at least 12 different positions along the thickness direction of the negative electrode sheet 521 (not including the ferroelectric layer 5213) can be measured with a micrometer, and the average value can be set as the thickness h1 of the negative electrode sheet 521. Next, the thickness of the negative electrode sheet 521 at at least 12 different positions along the thickness direction of the negative electrode sheet 521 (including the ferroelectric layer 5213) can be measured with a micrometer, and the average value can be set as the thickness h2 of the negative electrode sheet 521, and the thickness H of the ferroelectric layer 5213 is h2-h1.
[0052] The thickness of the ferroelectric layer 5213 can also be measured directly by tomographic scanning. Specifically, 1. Preparation of the sample: a. Cut the pole piece into 6mm x 6mm size with ceramic scissors, attach it to a sample stage coated with paraffin, and allow the sample to protrude slightly (<1mm) from the edge of the sample stage. b. Set the polishing voltage and time polishing (100min under 7.5KV for a negative electrode sheet with a thickness of 150um). 2. Morphological analysis: Using a scanning electron microscope, move the sample position at about 50x magnification until it becomes clear, take the thickness of each of the 12 position marks 5213, and take the average value at the end to obtain the thickness of 5213.
[0053] In some embodiments, the ferroelectric particles have a volume average particle size Dv50 of D μm, where 0.08≦D≦1.
[0054] The volume average particle diameter Dv50 of the ferroelectric particles satisfying the above range is advantageous for uniform distribution in the ferroelectric layer 5213. During the charging process of the secondary battery, each ferroelectric particle excites the ferroelectric effect to generate a reverse electric field, and an appropriate particle diameter ensures that the reverse electric fields between the ferroelectric particles do not interfere with each other, and the strength of the electric field of each ferroelectric particle is guaranteed, thereby ensuring the effect of the ferroelectric particles to homogenize the metal ions. In addition, the ferroelectric particles with the above volume average particle diameter are easy to manufacture and mold, and the process is simple, while if the particle diameter is too small, the production process is complicated and the cost is relatively high. Preferably, 0.1≦D≦0.8 μm, and for example, D μm may be 0.08 μm, 0.09 μm, 0.10 μm, 0.15 μm, 0.20 μm, 0.25 μm, 0.30 μm, 0.35 μm, 0.40 μm, 0.50 μm, 0.60 μm, 0.70 μm, 0.80 μm, or 0.90 μm, or a range consisting of any two of the above numerical values.
[0055] In this application, the volume average particle size Dv50 of a material has a meaning known in the art, and indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be tested by devices and methods known in the art. For example, referring to GB / T19077-2016 Particle Size Distribution Laser Diffraction Method, it can be easily tested using a laser particle size analyzer, for example, the Mastersizer2000E type laser particle size analyzer manufactured by Malvern Instruments, UK.
[0056] In some embodiments, the mass content a of the ferroelectric particles satisfies 90%≦a≦98%, preferably 95%≦a≦98%, based on the total mass of the ferroelectric layer 5213.
[0057] When the mass content a of the ferroelectric particles satisfies the above range, the ferroelectric particles are more uniformly distributed on the surface of the negative electrode film layer 5212, the generated reverse electric field becomes more uniform, and the adhesion between the ferroelectric layer 5213 containing the ferroelectric particles and the negative electrode sheet is good, thereby improving the stability of the ferroelectric layer.
[0058] When fabricating the ferroelectric layer 5213, a ferroelectric slurry containing ferroelectric particles is used. The ferroelectric slurry is placed on the surface of the negative electrode film layer 5212 and solidified to form the ferroelectric layer 5213. By adjusting the solid content of the ferroelectric particles in the ferroelectric slurry, the mass content a of the ferroelectric particles in the ferroelectric layer 5213 can be adjusted.
[0059] In some embodiments, the ferroelectric particles include one or a combination of multiple types selected from perovskite structure oxides, tungsten bronze type compounds, and bismuth oxide type layered structure compounds. More preferably, the ferroelectric particles 103 are selected from perovskite structure oxides.
[0060] Preferably, the perovskite structure oxide has the molecular formula Ba 1-x A x Ti 1-y B y O3. A includes one or a combination of multiple types selected from Pb, Sr, Ca, K, Na, and Cd, B includes one or a combination of multiple types selected from Sn, Hf, Zr, Ce, Nb, and Th, and 0 ≦ x ≦ 1, 0 ≦ y ≦ 1. For example, the perovskite structure oxide may include one or a combination of multiple types selected from BaTiO3, Ba 1-x1 Sr x1 TiO3 (0 ≦ x1 ≦ 1), SrTiO3, PbTiO3, PbZr y1 Ti 1-y1 O3 (0 ≦ y1 ≦ 1), BaZr y2 Ti 1-y2 O3 (0 < y2 < 1), KNbO3, and NaNbO3. Furthermore, the ferroelectric particles may include one or more of barium titanate BTO, lead zirconate titanate PZT, lead metaniobate, lead barium lithium niobate PBLN, and lead titanate PT. The above types of ferroelectric particles can effectively exhibit the ferroelectric effect and enhance the degree of uniform distribution of metal ions.
[0061] Preferably, the tungsten bronze type compound has the molecular formula M zIt may have WO3. M includes one or more combinations selected from Na, K, Rb, and Cs, and 0 < z < 1. For example, the tungsten bronze-type compound is Na z1 WO3 (0 < z1 < 1), K z2 WO3 (0 < z2 < 1) may include one or more combinations selected therefrom.
[0062] Preferably, the bismuth oxide-type layered structure compound has the molecular formula (Bi2O2)(C n-1 D n O 3n+1 ). C includes one or more combinations selected from Na, K, Ba, Sr, Pb, Ca, Ln, and Bi, D includes one or more combinations selected from Zr, Cr, Nb, Ta, Mo, W, Fe, Ti, and V, and 2 ≤ n ≤ 5. For example, the bismuth oxide-type layered structure compound may be one or more combinations of SrBi2Nb2O9, SrBi2Ta2O9, SrBi2Nb2O9, Bi4Ti3O 12 .
[0063] In some embodiments, the dielectric constant of the ferroelectric particles satisfies 100 ≤ ε ≤ 100000.
[0064] When the dielectric constant of the ferroelectric particles is within the above range, it has the effect of rapidly moving metal ions and can guarantee the moving speed of metal ions. Preferably, 1000 ≤ ε ≤ 10000. Exemplarily, the dielectric constant of the ferroelectric particles may be 100 - 50000, 100 - 25000, 100 - 10000, 100 - 5000, 100 - 4000, 100 - 3000, 100 - 2000, 100 - 1000, 100 - 500, 150 - 50000, 150 - 25000, 150 - 10000, 150 - 5000, 150 - 4000, 150 - 3000, 150 - 2000, 150 - 1000, 150 - 500, 200 - 50000, 200 - 25000, 200 - 10000, 200 - 5000, 200 - 4000, 200 - 3000, 200 - 2000, or 200 - 1000.
[0065] In this application, the dielectric constant of the ferroelectric particles refers to the dielectric constant at room temperature (25±5°C), has a meaning known in the art, and can be tested by devices and methods known in the art. For example, after the ferroelectric particles are made into a circular sample, the capacitance C can be tested using an LCR meter, and the dielectric constant ε can be calculated by the formula ε=(C×d) / (ε0×A). C represents the capacitance in farads (F), d represents the thickness of the sample in cm, and A represents the area of the sample in cm. 2 where ε0 is the vacuum dielectric constant, ε0=8.854×10 -14 F / cm. In this application, the test conditions may be 1KHz, 1.0V, 25±5℃. The test standard may be in accordance with GB / T11297.11-2015. When preparing the sample, reference may be made to Chinese patent application CN114217139A.
[0066] In some embodiments, the ferroelectric layer 5213 further includes an adhesive, and the adhesive can include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0067] In some embodiments, the ferroelectric layer 5213 further comprises a dispersant, which may include one or more of the following: sodium carboxymethylcellulose, polyvinylpyrrolidone, and Hypermer KD-1.
[0068] In some embodiments, the ferroelectric layer 5213 further includes other auxiliary agents, such as a conductive agent, which can improve the migration speed of metal ions in the ferroelectric layer 5213 and ensure the rapid charging capability of the secondary battery. Exemplarily, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0069] In some embodiments, the compressed density of the negative electrode membrane layer 5212 is Pg / cm 3 and the coating weight CWg / 1540.25 mm of the negative electrode film layer 5212 2 The following relationship is satisfied between JPEG2025503038000008.jpg1653
[0070] And the result is as follows: JPEG2025503038000009.jpg1942
[0071] When the compression density P and coating weight CW of the negative electrode film layer satisfy the above range, it can be ensured that the negative electrode film layer is within an appropriate thickness range, thereby ensuring the energy density of the secondary battery. When Z is within the above range during the charging process of the secondary battery, the ferroelectric layer affects the entire structure of the pole piece, including the structure of the lower layer of the pole piece. In addition, the pole piece has an appropriate void, and the electrolyte is sufficiently infiltrated into the pole piece, which is favorable for the movement of lithium ions. Preferably, Z may be 5 to 27, and may be, for example, 5, 10, 15, 20, 25, or 27, or a range consisting of any two of the above values.
[0072] In some embodiments, the compressed density of the negative electrode film layer 5212 is Pg / cm 3 satisfies 1.10≦P≦1.85.
[0073] By adjusting the compression density of the negative electrode film layer 5212 within an appropriate range, the energy density of the secondary battery can be increased. In addition, by adjusting the compression density within an appropriate range, the negative electrode film layer 5212 has the ability to maintain a strong channel structure during cycling, which improves the wettability of the electrolyte of the negative electrode sheet 521, and can further improve the cycle performance of the secondary battery. Preferably, 1.30≦P≦1.80. For example, Pg / cm 3 is 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 or 1.8 g / cm 3 or the value of P is within any two of the above numerical ranges.
[0074] In this application, the compression density of a material has a meaning known in the art, and can be tested by equipment and methods known in the art. For example, it can be tested by an electronic pressure test machine (e.g., UTM7305 type) with reference to standard GB / T24533-2009. An exemplary test method is as follows: 1 g of material is weighed and the base area is 1.327 cm 2 The material was placed in a mold, pressurized to 2000 kg (equivalent to 20,000 N), and held for 30 seconds, after which the pressure was released and held for 10 s, and the compressed density of the material at an applied force of 20,000 N was recorded and calculated.
[0075] In some embodiments, the coating weight of the negative electrode film layer 5212 is CWg / 1540.25 mm 2 satisfies 0.1≦CW≦0.3.
[0076] By adjusting the coating weight CW of the negative electrode film layer 5212 within a suitable range, the energy density of the electric core and the effect of the ferroelectric layer 5213 on the negative electrode film layer can be ensured. Preferably, 0.14≦CW≦0.2. For example, CWg / 1540.25mm 20.1g / 1540.25mm 2 , 0.12g / 1540.25mm 2 , 0.14g / 1540.25mm 2 , 0.16g / 1540.25mm 2 , 0.18g / 1540.25mm 2 Or 0.2g / 1540.25mm 2 may be also possible.
[0077] How to measure the coat weight (CW):
[0078] The substrate punching area is 1540.25 mm 2 and weigh it on a balance. A small circular piece (area: 1540.25 mm 2 ) can be punched out, weighed, and the weight of the substrate subtracted to obtain the applied weight of the active material.
[0079] In some embodiments, the thickness L μm of the negative electrode film layer 5212 satisfies 30 μm≦L≦200 μm.
[0080] By adjusting the thickness L of the negative electrode film layer 5212 within an appropriate range, the quality of the negative electrode active material can be ensured, and the energy density of the secondary battery can be ensured, while the ferroelectric layer 5213 can cooperate with the ferroelectric layer 5213 to fully exert the ferroelectric effect, and the uniform distribution of metal ions in the negative electrode film layer 5212 can be promoted. Preferably, 35 μm≦L≦190 μm. Exemplarily, L may be 30, 35, 40, 45, 50, 60, 70, 80, 90, 100, 120, 140, 150, 160, 180, 190, or 200, or a range consisting of any two of the above values.
[0081] In the present application, the thickness of the negative electrode film layer 5212 has a meaning known in the art, and can be measured using equipment and methods known in the art. For example, the thickness of the negative electrode sheet 521 (not including the ferroelectric layer 5213) can be measured with a micrometer at at least 12 different positions along the thickness direction of the negative electrode sheet 521, the average value is set as the thickness h1 of the negative electrode sheet 521, and then the thickness of the negative electrode current collector 5211 is subtracted to obtain the thickness of the negative electrode film layer 5212.
[0082] The thickness of the negative electrode film layer 5212 can also be measured directly by tomographic scanning, specifically, the coating weight can be measured by ion abrasion scanning. 1. Sample preparation: a. Cut the pole piece into 6mm x 6mm size with ceramic scissors, attach it to a sample stage coated with paraffin, and allow the sample to protrude slightly (<1mm) from the edge of the sample stage. b. Set the polishing voltage and time polishing (100min under 7.5KV for a 150um thick negative electrode sheet). 2. Morphological analysis: Using a scanning electron microscope, move the sample position at about 50x magnification until it becomes clear, take the thickness of each of the 12 position marks 5212, and take the average value at the end to obtain the thickness of 5212.
[0083] In some embodiments, the negative electrode film layer 5212 may include a negative electrode active material for a secondary battery known in the art. For example, the negative electrode active material may include one or more combinations selected from natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include one or more combinations selected from elemental silicon, silicon oxide, silicon carbon composite, silicon nitrogen composite, and silicon alloy material. The tin-based material may include one or more combinations selected from elemental tin, tin oxide, and tin alloy material. More preferably, the negative electrode active material includes a silicon carbon composite, and during the charging process of the secondary battery, the silicon in the silicon carbon composite expands in volume, and the expanded silicon provides a certain compressive stress to the ferroelectric particles, which can further excite the piezoelectric effect of the ferroelectric particles and enhance the ability to uniform the concentration of metal ions.
[0084] In some embodiments, the negative electrode film layer 5212 may further include a negative electrode conductive agent, if necessary. In the present application, the type of the negative electrode conductive agent is not particularly limited, and as an example, the negative electrode conductive agent may include one or a combination of a plurality of types selected from superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is 5% or less with respect to the total mass of the negative electrode film layer 5212.
[0085] In some embodiments, the negative electrode film layer 5212 may further include a negative electrode adhesive, if necessary. In the present application, the type of the negative electrode adhesive is not particularly limited. As an example, the negative electrode adhesive may include one or more combinations selected from styrene butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-soluble acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage content of the negative electrode adhesive is 5% or less with respect to the total mass of the negative electrode film layer 5212.
[0086] In some embodiments, the negative electrode membrane layer 5212 may further include other auxiliary agents as necessary. For example, the other auxiliary agents may include a thickener such as sodium carboxymethyl cellulose (CMC-Na), a PTC thermistor material, etc. In some embodiments, the mass percentage content of the other auxiliary agents is 2% or less with respect to the total mass of the negative electrode membrane layer 5212.
[0087] In some embodiments, the negative electrode current collector 5211 may be a metal foil piece or a composite current collector. Examples of the metal foil piece include copper foil and copper alloy foil. The composite current collector may include a polymeric material base layer and a metal material layer formed on at least one surface of the polymeric material base layer. For example, the metal material may include one or more combinations selected from copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, and the polymeric material base layer may include one or more combinations selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0088] The negative electrode membrane layer 5212 is typically formed by applying a negative electrode slurry to the negative electrode current collector 5211, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional adhesive, and other optional auxiliary agents in a solvent, and stirring uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.
[0089] The negative electrode sheet 521 does not exclude other additional functional layers except the negative electrode film layer 5212. For example, in some embodiments, the negative electrode sheet 521 of the present application is sandwiched between the negative electrode current collector 5211 and the negative electrode film layer 5212 and further includes a conductive primer layer (e.g., made of a conductive agent and an adhesive) provided on the surface of the negative electrode current collector 5211. In some other embodiments, the negative electrode sheet 521 of the present application further includes a protective layer covering the surface of the negative electrode film layer 5212.
[0090] In addition, the above-mentioned test of various parameters for the negative electrode sheet 521 has been described as an example in which the negative electrode active material is used as a test sample, but the test may be performed by sampling before the application of the negative electrode slurry, or by sampling from the negative electrode film layer 5212 after cold pressing. When the test sample of the negative electrode sheet 521 is sampled from the negative electrode film layer 5212 after cold pressing, the sampling can be performed by the following steps, for example. The cold-pressed negative electrode film layer 5212 is arbitrarily selected, and the negative electrode active material is sampled (for example, the powder may be scraped off using a blade for sampling). The collected negative electrode active material powder is placed in deionized water, suction filtered, and dried, and the dried negative electrode active material is sintered at a certain temperature and time (for example, 400°C, 2h), and the adhesive and conductive agent are removed to obtain a test sample of the negative electrode active material. When the ferroelectric particles are used as a test sample, the test may be performed by sampling before the hardening of the ferroelectric slurry, or by sampling after the hardening of the ferroelectric slurry.
[0091] Method for producing negative electrode sheet
[0092] According to a second aspect, the present application further provides a method for producing a negative electrode sheet, which may be used to produce a negative electrode sheet according to any embodiment of the first aspect of the present application.
[0093] The method includes the following steps.
[0094] S100 provides a negative electrode current collector.
[0095] In S200, a negative electrode slurry including a negative electrode active material is supplied to the negative electrode current collector, and a negative electrode film layer is formed by curing on at least one surface of the negative electrode current collector.
[0096] In S300, a ferroelectric slurry containing ferroelectric particles is supplied to the negative electrode film layer, and a ferroelectric layer is formed by hardening on the surface of the negative electrode film layer away from the negative electrode current collector, thereby obtaining a negative electrode sheet.
[0097] Here, the compression density of the negative electrode film layer is Pg / cm 3 It is.
[0098] The coating weight of the negative electrode film layer is CWg / 1540.25mm 2 It is.
[0099] The ferroelectric layer has a thickness of H μm.
[0100] The volume average particle size Dv50 of the ferroelectric particles is D μm.
[0101] The negative electrode sheet satisfies the following relationship. JPEG2025503038000010.jpg3580
[0102] The method of the embodiment of the present application has a simple fabrication process, does not require changing the original production process route, and only requires continuing to form a ferroelectric layer on the negative electrode film layer, making the operation convenient, and the formed negative electrode sheet has good dynamic performance.
[0103] In some embodiments, in step S200, the mass content a of the ferroelectric particles satisfies 90%≦a≦98%, preferably 95%≦a≦98%, based on the total mass of the ferroelectric layer.
[0104] The ferroelectric slurry may be provided on the negative electrode film layer using a number of processes, such as a gravure process, a coating process, etc. Specifically, when the gravure process is adopted, the ferroelectric slurry is placed on a gravure disk, and the gravure roll carries the ferroelectric slurry through a roll gap and rolls over the negative electrode film layer, and the thickness of the ferroelectric layer can be controlled by adjusting the dimension of the roll gap.
[0105] When the mass of the ferroelectric slurry is small, the ferroelectric slurry may partially cover the negative electrode film layer, and the ferroelectric layer formed by hardening may be continuous or discontinuous. As the mass of the ferroelectric slurry increases, the ferroelectric slurry may entirely cover the negative electrode film layer, and the ferroelectric layer formed by hardening may be continuous and the entire layer is covered by the negative electrode film layer.
[0106] The mass of the ferroelectric particles can be adjusted by adjusting the mass content a of the ferroelectric particles. When the mass content a of the ferroelectric particles is within the above range, the bonding strength between the ferroelectric layer and the negative electrode film layer is high, the ferroelectric layer is not easily peeled off, the ferroelectric layer easily exerts the ferroelectric effect, and it is easy to uniformize the distribution of metal ions.
[0107] secondary battery
[0108] According to a third aspect, the present application provides a secondary battery including the negative electrode sheet of the second aspect of the present application.
[0109] A secondary battery, also called a rechargeable battery or storage battery, is a battery that can be used continuously after being discharged by activating the active material through charging. A secondary battery includes an electrode assembly and an electrolyte.
[0110] As shown in Fig. 3, the electrode assembly 52 typically includes a positive electrode sheet 522, a negative electrode sheet 521, and a separator 523. The separator 523 is provided between the positive electrode sheet 522 and the negative electrode sheet 521, and mainly serves to prevent short-circuiting between the positive electrode and the negative electrode, while allowing metal ions to pass through. The electrolyte serves to conduct metal ions between the positive electrode sheet 522 and the negative electrode sheet 521. The secondary battery of the present application may be a lithium secondary battery, a sodium ion battery, etc., and may in particular be a lithium ion secondary battery.
[0111] [Negative electrode sheet]
[0112] The negative electrode sheet used in the secondary battery of the present application is the negative electrode sheet of any of the embodiments of the second aspect of the present application.
[0113] [Positive electrode sheet]
[0114] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, for example, the positive electrode current collector has two opposing surfaces in a thickness direction of the positive electrode current collector, and the positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.
[0115] The positive electrode film layer contains a positive electrode active material, and the positive electrode active material may employ a positive electrode active material known in the art for secondary batteries. For example, the positive electrode active material may include one or a combination of multiple types selected from lithium transition metal oxides, lithium-containing phosphates having an olivine structure, and their respective modified compounds. Examples of the lithium transition metal oxide may include one or a combination of multiple types selected from lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphate having an olivine structure may include one or a combination of two or more types selected from lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their modified compounds.
[0116] In some embodiments, in order to further increase the energy density of the secondary battery, the positive electrode active material may include one or a combination of multiple types of the lithium transition metal oxide represented by Formula 1 and its modified compounds.
[0117] Li a Ni b Co c M d O e A f Formula 1
[0118] In Formula 1, 0.8 ≦ a ≦ 1.2, 0.5 ≦ b < 1, 0 < c < 1, 0 < d < 1, 1 ≦ e ≦ 2, 0 ≦ f ≦ 1, M includes one or a combination of multiple types selected from Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A includes one or a combination of multiple types selected from N, F, S, and Cl.
[0119] In the present application, the modified compound of each positive electrode active material may perform doping modification and / or surface coating modification on the positive electrode active material.
[0120] In some embodiments, the positive electrode film layer may contain a positive electrode conductive agent as necessary. In the present application, the type of the positive electrode conductive agent is not particularly limited, but as an example, the positive electrode conductive agent may include one or a combination of a plurality of types selected from superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage content of the positive electrode conductive agent is 5% or less with respect to the total mass of the positive electrode film layer.
[0121] In some embodiments, the positive electrode film layer may include a positive electrode adhesive as necessary. In the present application, the type of the positive electrode adhesive is not particularly limited, but as an example, the positive electrode adhesive may include one or more combinations selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. In some embodiments, the mass percentage content of the positive electrode adhesive is 5% or less with respect to the total mass of the positive electrode film layer.
[0122] In some embodiments, the positive electrode current collector may be a metal foil piece or a composite current collector. Examples of the metal foil piece include aluminum foil or aluminum alloy foil. The composite current collector may include a polymeric material base layer and a metal material layer formed on at least one surface of the polymeric material base layer. For example, the metal material may include one or more combinations selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, and the polymeric material base layer may include one or more combinations selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0123] The positive electrode membrane layer is usually formed by applying a positive electrode slurry to a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is usually formed by dispersing a positive electrode active material, an optional conductive agent, an optional adhesive, and any other components in a solvent, and stirring the mixture uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).
[0124] [Electrolyte]
[0125] The electrolyte of the present application may be any electrolyte for secondary batteries known in the art, and includes a lithium salt and an organic solvent.
[0126] As an example, the lithium salt may include one or more combinations selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonylimide (LiFSI), lithium bistrifluoromethanesulfonylimide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium bisoxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).
[0127] By way of example, the organic solvent may include at least one or a combination of more than one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0128] [Separator]
[0129] In the present application, the type of the separator is not particularly limited, and any known porous structure separator having good chemical stability and mechanical stability can be selected.
[0130] In some embodiments, the separator may be made of a material selected from the group consisting of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of the layers may be the same or different.
[0131] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly by a rolling process or a stacking process.
[0132] In some embodiments, the secondary battery can include an exterior case that can be used to seal the electrode assembly and the electrolyte.
[0133] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a soft package, such as a bag-type soft package. The material of the soft package may be, for example, plastic, such as one or a combination of multiple types of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0134] In the present application, the shape of the secondary battery is not particularly limited, and may be cylindrical, rectangular, or any other shape. For example, FIG. 4 shows a secondary battery 5 having a rectangular structure as an example.
[0135] In some embodiments, as shown in FIG. 5, the exterior may include a case 51 and a cover plate 53. The case 51 includes a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are surrounded to form a chamber. The case 51 has an opening communicating with the chamber, and the cover plate 53 covers the opening to close the chamber. The positive electrode sheet, the negative electrode sheet and the separator may form an electrode assembly 52 by a winding process or a lamination process. The electrode assembly 52 is sealed in the chamber. The electrode assembly 52 is infiltrated with an electrolyte. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and may be adjusted according to needs.
[0136] The method of fabricating the secondary battery of the present application is known. In some embodiments, a secondary battery can be formed by assembling a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. For example, a positive electrode sheet, a separator, and a negative electrode sheet can be formed into an electrode assembly by a winding process or a lamination process, and the electrode assembly can be placed in an outer casing, dried, and then an electrolyte can be injected, and a secondary battery can be obtained through processes such as vacuum sealing, standing, chemical formation, and shaping.
[0137] In some embodiments of the present application, the secondary battery of the present application may be assembled into a battery module, and the number of secondary batteries included in the battery module may be multiple, and the specific number may be adjusted according to the application and capacity of the battery module.
[0138] Fig. 6 is a schematic diagram of an example battery module 4. As shown in Fig. 6, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by a fastener.
[0139] Preferably, the battery module 4 further includes a housing having an accommodation space, and the multiple secondary batteries 5 are accommodated in the accommodation space.
[0140] In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules included in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0141] 7 and 8 are schematic diagrams of an example battery pack 1. As shown in Fig. 7 and Fig. 8, the battery pack 1 may include a battery box and a plurality of battery modules 4 provided in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 is covered by the lower housing 3 to form an enclosed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0142] power consumption equipment
[0143] In a fourth aspect, the present application provides a power consuming device including at least one of the secondary battery, battery module, and battery pack of the present application. The secondary battery, battery module, and battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0144] A power consuming device can select a secondary battery, a battery module, or a battery pack according to its usage needs.
[0145] 9 is a schematic diagram of an example power consuming device 6, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack 1 or a battery module can be employed to meet the high power and high energy density demands of the power consuming device.
[0146] Other examples of power consuming devices may be mobile phones, tablet computers, notebook computers, etc. Such power consuming devices are usually required to be thin and may employ secondary batteries as their power source.
[0147] Working Example
[0148] The following examples of the present application are described. The examples described below are illustrative and are merely for the purpose of interpreting the present application, and cannot be understood as limitations on the present application. Unless specific techniques or conditions are specified in the examples, the techniques or conditions or product instructions are performed according to those described in the literature in this field. Reagents and instruments used that do not specify the manufacturer are ordinary products that are commercially available.
[0149] Example 1
[0150] 1. Preparation of Positive Electrode Sheet
[0151] As the positive electrode current collector, an aluminum foil having a thickness of 13 μm was used.
[0152] Positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black, and polyvinylidene fluoride (PVDF) as an adhesive were thoroughly mixed in a weight ratio of 98:1:1 in an appropriate amount of N-methylpyrrolidone (NMP) solvent to form a uniform positive electrode slurry. The positive electrode slurry was then applied to the surface of a positive electrode current collector, and after processes such as drying, a positive electrode sheet was obtained.
[0153] 2. Preparation of negative electrode sheet
[0154] 2.1 Preparation of negative electrode active material
[0155] The coke raw material was pretreated to remove impurities, and then pyrolysis and granulation were performed to obtain secondary particles with a Dv50 of 10 μm. Next, the coke raw material was graphitized at 3000°C for 24 hours, after which it was covered with asphalt and subjected to high-temperature carbonization at 1000°C for 15 hours to obtain artificial graphite.
[0156] 2.2 Preparation of the negative electrode film layer
[0157] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.
[0158] The negative electrode active materials, artificial graphite, conductive carbon black, thickener sodium carboxymethylcellulose (CMC), and adhesive styrene butadiene rubber emulsion (SBR), were thoroughly mixed and stirred in a weight ratio of 96.8:0.8:1.2:1.2 with an appropriate amount of deionized water to form a uniform negative electrode slurry. The negative electrode slurry was then applied to the negative electrode current collector, and after drying and other processes, a negative electrode film layer was obtained.
[0159] 2.3 Preparation of ferroelectric layer
[0160] 40 wt% barium titanate, styrene butadiene rubber (SR-1B) as an adhesive, sodium carboxymethylcellulose as a dispersant, and acrylic ester emulsion were dissolved in deionized water and stirred with a vacuum mixer until the system became uniform, obtaining barium titanate slurry with a solid content of 40%.
[0161] The barium titanate slurry was applied to the surface of the negative electrode film layer away from the negative electrode current collector and dried at 110°C. The barium titanate slurry was then hardened and molded into a ferroelectric layer in the negative electrode film layer, and then subjected to processes such as tab forming and slitting to obtain a negative electrode sheet.
[0162] 3. Preparation of Electrolyte
[0163] In an environment with a water content of less than 10 ppm, nonaqueous organic solvents ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent, and then lithium salt LiPF6 was dissolved in the mixed solvent to obtain an electrolyte with a lithium salt concentration of 1 mol / L.
[0164] 4. Preparation of the separator
[0165] A polyethylene film was selected as the separator, and was slit to obtain appropriate dimensions according to the dimensions of the positive and negative electrode sheets.
[0166] 5. Fabrication of Li-ion Batteries
[0167] The positive electrode sheet, separator, and negative electrode sheet are stacked in this order, and a separator is placed between the positive electrode sheet and the negative electrode sheet to serve as an insulator, and then the stack is wound to obtain an electrode assembly. The electrode assembly is placed in an exterior case, dried, and then an electrolyte is injected. The lithium-ion battery is obtained through processes such as vacuum sealing, standing, chemical formation, and shaping.
[0168] Example 2
[0169] Examples 2-1 to 2-7
[0170] Unlike Example 1, in Examples 2-1 to 2-5, the "thickness H of the ferroelectric layer" was adjusted.
[0171] Comparative Example
[0172] Comparative Example 1
[0173] Unlike Example 1, Comparative Example 1 does not employ a ferroelectric layer, and S=0.
[0174] Comparative Example 2
[0175] Unlike Example 1, in Comparative Example 2, the "thickness H of the ferroelectric layer" was adjusted.
[0176] Comparative Example 3
[0177] Unlike Example 1, in the negative electrode slurry of Comparative Example 3, the negative electrode active material and ferroelectric particles were mixed. Specifically, the negative electrode active material, ferroelectric particles BaTiO3, styrene butadiene rubber (SBR) as an adhesive, sodium carboxymethyl cellulose (CMC-Na) as a thickener, and carbon black as a conductive agent were thoroughly stirred and mixed in a mass ratio of 97:1:1:1 in an appropriate amount of deionized water as a solvent to form a uniform negative electrode slurry. The negative electrode slurry was uniformly applied to the surface of a negative electrode current collector copper foil, dried, and cold-pressed to obtain a negative electrode sheet.
[0178] The parameters of Example 1, Example 2, and Comparative Examples 1 to 3 are shown in Table 1.
[0179] [Table 1]
[0180] In this specification, it is as follows: JPEG2025503038000012.jpg3468
[0181] Example 3
[0182] Examples 3-1 to 3-4
[0183] Unlike Example 1, the particle size D of the ferroelectric particles was adjusted in Examples 3-1 to 3-4.
[0184] The parameters of Example 1 and Example 3-1 to Example 3-4 are shown in Table 2.
[0185] [Table 2]
[0186] Example 4
[0187] Example 4-1 to Example 4-4
[0188] Unlike Example 1, the mass content a % of the ferroelectric particles was adjusted in Examples 4-1 to 4-4.
[0189] The parameters of Example 1, and Example 4-1 to Example 4-4 are shown in Table 3.
[0190] [Table 3]
[0191] Example 5
[0192] Examples 5-1 to 5-5
[0193] Unlike Example 1, in Examples 5-1 to 5-5, the compressed density P and coating weight of the negative electrode film layer were adjusted.
[0194] The parameters of Example 1 and Example 5-1 to Example 5-5 are shown in Table 4.
[0195] [Table 4]
[0196] Example 6
[0197] Example 6-1 and Example 6-2
[0198] Unlike Example 1, the type of ferroelectric particles was adjusted in Examples 6-1 and 6-2.
[0199] Comparative Example 4
[0200] Unlike Example 1, in Comparative Example 4, the ferroelectric particles were replaced with alumina particles.
[0201] The parameters of Example 1, Example 6-1 and Example 6-2, and Comparative Example 4 are shown in Table 5.
[0202] [Table 5]
[0203] Testing part
[0204] 1. Test area of negative electrode sheet
[0205] 1.1 Coating weight of negative electrode film layer CW
[0206] 1540.25mm 2 The substrate is taken, weighed to W1 on a balance, and cold pressed to punch out pole pieces. The punched area is 1540.25 mm 2 The coating weight of the negative electrode film layer is CW=W2-W1, and is measured using a balance.
[0207] 1.2 Thickness of the negative electrode film layer L
[0208] The thickness of the negative electrode sheet (not including the ferroelectric layer) is measured with a micrometer at at least 12 different positions along the thickness direction of the negative electrode sheet, and the average value is set as the thickness H1 of the negative electrode sheet. Then, the thickness of the negative electrode current collector is subtracted from the average value to obtain the thickness of the negative electrode film layer.
[0209] 1.3 Compressed density P of the negative electrode film layer
[0210] The compression density of the negative electrode film layer is obtained by the coating weight CW of the film layer and the thickness L of the negative electrode film layer, and the calculation formula is P=CW / L / 1540.25.
[0211] 1.4 Thickness of ferroelectric layer H
[0212] The thickness of the negative electrode sheet (not including the ferroelectric layer) is measured at least at 12 different positions along the thickness direction of the negative electrode sheet with a micrometer, and the average value is defined as the thickness H1 of the negative electrode sheet. Next, the thickness of the negative electrode sheet (including the ferroelectric layer) is measured at least at 12 different positions along the thickness direction of the negative electrode sheet with a micrometer, and the average value is defined as the thickness h2 of the negative electrode sheet, and the thickness H of the ferroelectric layer is defined as H=h2-h1.
[0213] 1.5 Test method for particle size of ferroelectric particles
[0214] The Dv90, Dv50, and Dv10 of a material have the meanings known in the art and can be measured by instruments and methods known in the art. For example, refer to GB / T19077-2016 Particle Size Distribution Laser Diffraction Method, and can be easily tested using a laser particle size analyzer, such as the Mastersizer2000E laser particle size analyzer from Malvern, UK. Dv90 is the particle size corresponding to the material cumulative volume distribution percentage reaching 90%, Dv50 is the particle size corresponding to the material cumulative volume distribution percentage reaching 50%, and Dv10 is the particle size corresponding to the material cumulative volume distribution percentage reaching 10%.
[0215] 2. Secondary battery test section
[0216] 2.1 Secondary battery quick charging performance test
[0217] At 25°C, the lithium ion batteries prepared in the examples and comparative examples are fully charged at nC (for example, n=0.1, 0.2, 0.3, 0.4, 0.5) and fully discharged at 1C, and cycled in this manner 10 times. After the lithium ion batteries are fully charged at 1C, the negative electrode sheet is disassembled and the lithium deposition state on the surface of the negative electrode sheet is observed. If no lithium is deposited, the batteries are fully charged at (n+0.1)C and the test is performed again. In this manner, the charge rate is increased until lithium is deposited on the surface of the negative electrode, and 0.1C is subtracted from the multiplier at this time to determine the maximum charging capacity of the lithium ion battery.
[0218] 2.2 Energy density testing
[0219] At 25°C, the lithium ion batteries prepared in the Examples and Comparative Examples were fully charged at a rate of 0.33 C and fully discharged at a rate of 0.33 C, and cycled three times to obtain the discharge energy (E) of the last cycle. The mass (m) of the lithium ion battery was then measured using an electronic balance, where W = E / m.
[0220] 2.3 Shelf Life Testing
[0221] The lithium ion batteries prepared in the examples and comparative examples were fully charged to 97% state of charge (SOC) and stored at 60°C until the capacity was reduced to 80%, and the storage time was recorded. The target storage time was 280 days, and the ratio of the storage time to the target storage time was calculated for each of the examples and comparative examples to obtain the storage life. The target storage life was 100%.
[0222] 2.4 Cycling performance test
[0223] The lithium ion batteries prepared in the examples and comparative examples were charged at 3C at 25°C and discharged at 1C. An SOC cycle test was performed from 3% to 97% until the capacity of the lithium ion battery became less than 80% of the initial capacity, and the number of cycles was recorded.
[0224] Test Results
[0225] The effect of the negative electrode sheet of the present invention in improving the performance of a secondary battery is shown in Tables 6 to 10. [Table 6]
[0226] As can be seen from the test results of Examples 2-1 to 2-5 in Table 6, the thickness of the ferroelectric layer is increased, the effect of inhibiting lithium dendrites is improved, and the charging capacity of the secondary battery is improved. After the growth of lithium dendrites is inhibited, the cycle performance of the electric core is obviously improved and cycle hopping can be reduced. As can be seen from Comparative Example 1, in a secondary battery without a ferroelectric layer, the lithium dendrites of the negative electrode sheet gradually grow during the cycle process, which deteriorates the cycle performance. As can be seen from Comparative Example 2, if the ferroelectric layer is too thick, there is a limit to the improvement of the charging capacity, and on the contrary, it inhibits the shuttle of lithium ions and greatly deteriorates the energy density. As can be seen from Comparative Example 3, even if the negative electrode active material and the ferroelectric are physically mixed, the opposite electric field directions generated by the physically mixed ferroelectric are not unified and interfere with each other, so the effect of improving the charging capacity is worse than that of the coating layer.
[0227] [Table 7]
[0228] As can be seen from the test results of Examples 3-1 to 3-4 in Table 7, the smaller the grain size of the ferroelectric, the higher the uniformity of distribution in the coating layer, the more balanced the growth of lithium dendrites, and the smaller the concentration polarization, but the smaller the grain size, the more complicated the manufacturing process and the higher the cost. After the grain size is increased, the cost is reduced, but the interference field occurs between each grain size, which affects the effect of inhibiting lithium precipitation.
[0229] [Table 8]
[0230] As can be seen from the test results of Examples 4-1 to 4-4 in Table 8, the higher the content of the ferroelectric, the stronger the reverse electric field strength generated, the slower the vertical production speed of lithium dendrites, and the more lithium is reversibly deposited, improving the charging ability and cycle performance. However, if the content of the ferroelectric is too high, the content of the adhesive and dispersant will decrease, the adhesive force of the ferroelectric to the negative electrode film layer will decrease, and it will be very easy to fall off, and its effect will not be achieved.
[0231] [Table 9]
[0232] As can be seen from the test results of Examples 5-1 to 5-4 in Table 9, when Z is in the above range during the charging process of the secondary battery, the ferroelectric layer has an effect on the entire structure of the pole piece, including the structure of the lower layer of the pole piece. In addition, the pole piece has a suitable void, and the electrolyte is sufficiently infiltrated into the pole piece, which is favorable for the movement of lithium ions. Therefore, when P / CW is in a suitable range, the charging capacity and energy density of the electric core can be optimized.
[0233] [Table 10]
[0234] As can be seen from the test results of Example 1, Example 6-1 to Example 6-2, and Comparative Example 4 in Table 10, during the charging process of a secondary battery, the ferroelectric material can significantly improve the performance of the battery compared to general oxide materials.
[0235] Although the present application has been described with reference to the preferred embodiments, various improvements are possible without departing from the scope of the present application, and some of the components may be replaced with equivalents. In particular, as long as there is no structural contradiction, the technical features mentioned in each embodiment may be arbitrarily combined. The present application is not limited to the specific embodiments disclosed above, but includes all aspects included in the scope of the claims.
Claims
1. A negative electrode current collector; a negative electrode film layer provided on at least one surface of the negative electrode current collector and including a negative electrode active material; a ferroelectric layer provided on a surface of the negative electrode film layer away from the negative electrode current collector and containing ferroelectric particles, Where: The compressed density of the negative electrode film layer is Pg / cm 3 and The coating weight of the negative electrode film layer is CWg / 1540.25 mm 2 and The thickness of the ferroelectric layer is H μm; The volume average particle size Dv50 of the ferroelectric particles is D μm, The negative electrode sheet is and preferably Meet the negative electrode sheet.
2. 2. The negative electrode sheet according to claim 1, wherein the thickness H μm of the ferroelectric layer satisfies 2≦H≦10, preferably 4≦H≦6.
3. 3. The negative electrode sheet according to claim 1, wherein the volume average particle diameter Dv50 of the ferroelectric particles satisfies 0.08≦D≦1, preferably 0.1≦D≦0.
8.
4. The negative electrode sheet according to any one of claims 1 to 3, wherein the mass content a of the ferroelectric particles satisfies 90%≦a≦98%, preferably 95%≦a≦98%, with respect to the total mass of the ferroelectric layer.
5. the ferroelectric particles contain one or more types selected from the group consisting of perovskite structure oxides, tungsten bronze type compounds, and bismuth oxide type layer structure compounds; Preferably, the perovskite structure oxide includes one or more of barium titanate (BTO), lead zirconate titanate (PZT), lead metaniobate, barium lithium lead niobate (PBLN) and lead titanate (PT). The negative electrode sheet according to any one of claims 1 to 4.
6. The negative electrode sheet according to any one of claims 1 to 5, wherein the dielectric constant of the ferroelectric particles satisfies 100≦ε≦100,000, preferably 1,000≦ε≦10,000.
7. The compressed density of the negative electrode film layer Pg / cm 3 and the coating weight of the negative electrode film layer CWg / 1540.25 mm 2 Between The negative electrode sheet according to any one of claims 1 to 6, which satisfies the above.
8. The compressed density of the negative electrode film layer Pg / cm 3 The negative electrode sheet according to any one of claims 1 to 7, wherein P satisfies 1.10≦P≦1.85, preferably 1.30≦P≦1.
80.
9. Coating weight of the negative electrode film layer CWg / 1540.25 mm 2 The negative electrode sheet according to any one of claims 1 to 8, wherein CW satisfies 0.10≦CW≦0.30, preferably 0.14≦CW≦0.
20.
10. The negative electrode sheet according to any one of claims 1 to 9, wherein the thickness L μm of the negative electrode film layer satisfies 30 μm≦L≦200 μm, preferably 35 μm≦L≦190 μm.
11. The negative electrode active material includes one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based material, tin-based material, and lithium titanate. The negative electrode sheet according to any one of claims 1 to 10.
12. A secondary battery comprising the negative electrode sheet according to any one of claims 1 to 11.
13. A battery module comprising the secondary battery according to claim 12.
14. A battery pack comprising the battery module according to claim 13.
15. A power consuming device comprising the secondary battery according to claim 12, the battery module according to claim 13, or the battery pack according to claim 14.
Citation Information
Patent Citations
Lithium battery
JP2014056822A
Nonaqueous electrolyte secondary battery
JP2015076120A
Lithium ion battery
JP2016072226A
Electrode with insulation film, manufacturing method thereof, and lithium secondary battery comprising the same
US20210013512A1
Secondary cell
WO2017038327A1
Cited By
Resin-coated metal sheet for container
US12486089B2